Pengaruh Kepemimpinan Transformasional terhadap Green Banking dengan Green Organizational Citizenship Behavior sebagai Variabel Intervening dan Kesadaran Lingkungan sebagai Variabel Moderasi - Yulia Destiani; Anton Budi Santoso (Universitas Negeri Surabaya, 2026)
The increasing emphasis on sustainable finance has encouraged banking institutions to integrate environmental considerations into their business operations through green banking practices. However, empirical evidence regarding the organizational factors that drive green banking implementation remains limited, particularly concerning the roles of transformational leadership, Green Organizational Citizenship Behaviour (GOCB), and environmental awareness. This study aims to examine the effect of transformational leadership on green banking, with GOCB serving as a mediating variable and environmental awareness as a moderating variable. A quantitative approach was employed using descriptive and verification methods. Data were collected from 120 respondents selected through a saturated sampling technique and analysed using Structural Equation Modelling–Partial Least Squares (SEM-PLS). The results indicate that transformational leadership has a positive and significant effect on both green banking and GOCB. In addition, GOCB significantly mediates the relationship between transformational leadership and green banking, demonstrating the importance of employees’ voluntary pro-environmental behaviour in supporting sustainable banking initiatives. Conversely, environmental awareness does not significantly moderate the relationship between GOCB and green banking, suggesting that individual awareness alone is insufficient to strengthen green banking implementation without organizational support mechanisms. These findings highlight the critical role of leadership and employee behaviour in advancing sustainable banking practices. This study contributes to the green banking literature by providing an integrated model that explains how transformational leadership influences green banking through GOCB while simultaneously examining the moderating role of environmental awareness in the banking sector.